Pathogenic UBA1 variants associated with VEXAS syndrome in Japanese patients with relapsing polychondritis. Issue 8 (31st March 2021) - Tsuchida, Naomi; Kunishita, Yosuke; Uchiyama, Yuri; Kirino, Yohei; Enaka, Makiko; Yamaguchi, Yukie; Taguri, Masataka; Yamanaka, Shoji; Takase-Minegishi, Kaoru; Yoshimi, Ryusuke; Fujii, Satoshi; Nakajima, Hideaki; et al.
Abstract : Objectives: To determine clinical and genetic features of individuals with relapsing polychondritis (RP) likely caused by pathogenic somatic variants in ubiquitin-like modifier activating enzyme 1 ( UBA1 ). Methods: Fourteen patients with RP who met the Damiani and Levine criteria were recruited (12 men, 2 women; median onset age (IQR) 72.1 years (67.1–78.0)). Sanger sequencing of UBA1 was performed using genomic DNA from peripheral blood leukocytes or bone marrow tissue. Droplet digital PCR (ddPCR) and peptide nucleic acid (PNA)-clamping PCR were used to detect low-prevalence somatic variants. Clinical features of the patients were investigated retrospectively. Results: UBA1 was examined in 13 of the 14 patients; 73% (8/11) of the male patients had somatic UBA1 variants (c.121A>C, c.121A>G or c.122T>C resulting in p.Met41Leu, p.Met41Val or p.Met41Thr, respectively). All the variant-positive patients had systemic symptoms, including a significantly high prevalence of skin lesions. ddPCR detected low prevalence (0.14%) of somatic variant (c.121A>C) in one female patient, which was subsequently confirmed by PNA-clamping PCR. Conclusions: Genetic screening for pathogenic UBA1 variants should be considered in patients with RP, especially male patients with skin lesions. The somatic variant in UBA1 in the female patient is the first to be reported.